2014
DOI: 10.1175/jcli-d-14-00149.1
|View full text |Cite
|
Sign up to set email alerts
|

Subtropical Cyclones over the Southwestern South Atlantic: Climatological Aspects and Case Study

Abstract: Hurricane Catarina (2004) and subtropical storm Anita (2010) called attention to the development of subtropical cyclones (SCs) over the South Atlantic basin. Besides strong and organized storms, a large number of weaker, shallower cyclones with both extratropical and tropical characteristics form in the region, impacting the South American coast. The main focus of this study is to simulate a climatology of subtropical cyclones and their synoptic pattern over the South Atlantic, proposing a broader definition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
153
1
22

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(196 citation statements)
references
References 47 publications
20
153
1
22
Order By: Relevance
“…Flexpart model was used to find source regions for the atmospheric moisture present over the southeastern coast of Brazil (30.58–21.8°S and 49.58–35.58°W, hereafter RG1), during SC events. These events were selected by the criteria and tracking methods described in Gozzo et al [], which have identified the RG1 as the region of western South Atlantic where most of the SCs have their genesis. In a period of 36 years (January 1980 to December 2015) a total set of 150 SCs was used to identify source regions of the moisture present in RG1 in subtropical cyclogenesis time (defined as 1200 UTC of the day when the cyclone was first identified by the tracking algorithm).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Flexpart model was used to find source regions for the atmospheric moisture present over the southeastern coast of Brazil (30.58–21.8°S and 49.58–35.58°W, hereafter RG1), during SC events. These events were selected by the criteria and tracking methods described in Gozzo et al [], which have identified the RG1 as the region of western South Atlantic where most of the SCs have their genesis. In a period of 36 years (January 1980 to December 2015) a total set of 150 SCs was used to identify source regions of the moisture present in RG1 in subtropical cyclogenesis time (defined as 1200 UTC of the day when the cyclone was first identified by the tracking algorithm).…”
Section: Methodsmentioning
confidence: 99%
“…Subtropical cyclones are nonfrontal low‐pressure systems with a thermally hybrid core (warm at low levels and cold at upper levels) and intense convective activity that develop mostly over the oceanic areas. Their occurrence over South America, more specifically in the southwestern South Atlantic, is documented in a number of case studies [ McTaggart‐Cowan et al , ; Veiga et al , ; Pereira‐filho et al , ; Vianna et al , ; Dias Pinto et al , ], and the climatology of such systems is presented in Evans and Braun [] and Gozzo et al []. This is still an incipient research area, and a better comprehension of subtropical cyclone (SC) development is important in a theoretical point of view and also to improve operational weather forecast.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations